STUDI DESKRIPTIF GAMBARAN KUALITAS HIDUP WANITA DEWASA AWAL PASCA PERCERAIAN YANG BERSTATUS SINGLE PARENT PADA MASYARAKAT DI DESA SAWARAN KULON KABUPATEN LUMAJANG - Heru Kuswanto; Siti Atiyyatul Fahiroh; Fety Khosianah (Universitas Muhammadiyah Surabaya, 2025)
This study aims to describe the quality of life of post-divorce single-parent early adult women in Sawaran Kulon Village, Lumajang Regency. The approach used was qualitative with phenomenological methods. The study subjects consisted of three early adult women who had experienced divorce and were navigating the role of single parents. Data collection techniques were in-depth interviews, non-participatory observation, and documentation. The results indicated that post-divorce, the subjects experienced significant changes in physical, emotional, social, and spiritual aspects. They faced challenges related to economy, childcare, social stigma, feelings of loneliness and emotional exhaustion. However, the subjects also demonstrated adaptive efforts in rebuilding their lives, such as participating in training, strengthening relationships with their children, and increasing independence. Support from their immediate family and friends was a crucial factor in the recovery process. This study emphasizes the important role of the social environment, emotional support, and internal strengths in shaping a better quality of life for post-divorce single-parent women.